Visceral hybrid reconstruction of thoracoabdominal aortic aneurysm after open repair of type A aortic dissection by the Bentall procedure with the elephant trunk technique – A case report - Marjanović, Ivan; Šarac, Momir; Tomić, Aleksandar; Rusović, Siniša; Sekulović, Leposava; Leković, Marko; Bezmarević, Mihailo (Vojnosanitetski pregled, 2014)
Introduction. Reconstruction of chronic type B dissection and thoracoabdominal aortic aneurysm (TAAA) remaining after the emergency reconstruction of the ascending thoracic aorta and aortic arch for acute type A dissection represents one of the major surgical challenges. Complications of chronic type B dissection are aneurysmal formation and rupture of an aortic aneurysm with a high mortality rate. We presented a case of visceral hybrid reconstruction of TAAA secondary to chronic dissection type B after the Bentall procedure with the ’elephant trunk’ technique due to acute type A aortic dissection in a high-risk patient. Case report. A 62 year-old woman was admitted to our institution for reconstruction of Crawford type I TAAA secondary to chronic dissection. The patient had had an acute type A aortic dissection 3 years before and undergone reconstruction by the Bentall procedure with the ’elephant trunk’ technique with valve replacement. On admission the patient had coronary artery disease (myocardial infarction, two times in the past 3 years), congestive heart disease with ejection fraction of 25% and chronic obstructive pulmonary disease. On computed tomography (CT) of the aorta TAAA was revealed with a maximum diameter of 93 mm in the descending thoracic aorta secondary to chronic dissection. All the visceral arteries originated from the true lumen with exception of the celiac artery (CA), and the end of chronic dissection was below the origin of the superior mesenteric artery (SMA). The patient was operated on using surgical visceral reconstruction of the SMA, CA and the right renal artery (RRA) as the first procedure. Postoperative course was without complications. Endovascular TAAA reconstruction was performed as the second procedure one month later, when the ’elephant trunk’ was used as the proximal landing zone for the endograft, and distal landing zone was the level of origin of the RRA. Postoperatively, the patient had no neurological deficit and renal, liver function and functions of the other abdominal organs were normal. Control CT after 6 months showed full exclusion of the aneurysm from the systemic circulation without endoleak and good flow through visceral anastomosis. Conclusion. In patients with comorbidities, like in the presented case, visceral hybrid reconstruction of chronic dissection type B with TAAA could be the treatment of choice.